PERANCANGAN MOTIF TEKSTIL KONTEMPORER BERBASIS ISU BUDAYA POPULER DENGAN PRINSIP LOCALISM - Enrico Enrico; Ciawita Lautama; Evan Raditya Pratomo (Universitas Mercu Buana, 2022)
The fashion sub-sector is part of the creative economy sector (Ekraf) which is a contributor to GDP that contributes to lifting Indonesia's economic growth. The fashion industry will continue to offer differentiation and novelty in each of its products in order to be accepted by the public and consumers, one of the important aspects in the manufacture of fashion products is textiles. As an expression of expression and function of communication, fashion is a determinant of the lifestyle of urban communities. The design of this contemporary textile motif applies one of the principles of fashion sustainability, namely localism, by raising the issues of popular culture that became the inspiration in doing the design. The method used in this design applies the six stages of FRANGIPANI. This design produces 20 contemporary textile motifs using design principles ecspecially rhtym and emphasis, and 3 of them are realized into a resort fashion collection. It is hoped that the design of contemporary textile motifs can increase the interest of the younger generation to continue to advance the fashion industry and not forget Indonesian local culture.